The alternatively spliced form "b" of the Epithelial Sodium Channel α subunit (α ENaC): Any prior evidence of its existence? - Shehata, Marlene F. (Université d'Ottawa | University of Ottawa, 2010)
The epithelial sodium channel (ENaC) is critical in maintaining sodium balance across aldosterone-responsive epithelia. ENaC is a combined channel formed of three subunits (αβγ) with α ENaC subunit being the most critical for channel functionality. In a previous report, we have demonstrated the existence and mRNA expression levels of four alternatively spliced forms of the α ENaC subunit denoted by -a, -b, -c and -d in kidney cortex of Dahl S and R rats. Of the four alternatively spliced forms presently identified, α ENaC-b is considered the most interesting for the following reasons: Aside from being a salt-sensitive transcript, α ENaC-b mRNA expression is ∼32 fold higher than α ENaC wildtype in kidney cortex of Dahl rats. Additionally, the splice site used to generate α ENaC-b is conserved across species. Finally, α ENaC-b mRNA expression is significantly higher in salt-resistant Dahl R rats versus salt-sensitive Dahl S rats. As such, this commentary aims to highlight some of the previously published research articles that described the existence of an additional protein band on α ENaC western blots that could account for α ENaC-b in other rat species.